1992
DOI: 10.1021/ma00047a045
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorinated polyimide synthesis

Abstract: Polymers are expected to be used as media for transmitting near-infrared light in such optical communication applications as the waveguide in optoelectronic integrated circuits (OEIC) and in multichip interconnections.1-2 The current manufacturing process for ICs and multichip modules includes soldering at 260 °C and short-term processes at temperatures of up to 400 °C. Waveguide polymeric materials should therefore have high thermal stability-that is, a high glass transition temperature (Tg) and a high polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
83
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(83 citation statements)
references
References 1 publication
0
83
0
Order By: Relevance
“…The resulting birefringence of the cured polymer was ⌬n ϭ n TE Ϫ n TM ϳ 0.007 at 1.55 m. This is much lower than those of fluorinated polyimides developed for optical waveguides. 10 From the above optical results, we could design the optical devices based on the precise refractive index with low birefringence.…”
Section: Fluorinated Poly(arylene Ether)s Containing Phenyl Ethynyl Gmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting birefringence of the cured polymer was ⌬n ϭ n TE Ϫ n TM ϳ 0.007 at 1.55 m. This is much lower than those of fluorinated polyimides developed for optical waveguides. 10 From the above optical results, we could design the optical devices based on the precise refractive index with low birefringence.…”
Section: Fluorinated Poly(arylene Ether)s Containing Phenyl Ethynyl Gmentioning
confidence: 99%
“…8 Recently, the low-loss polymeric waveguide devices were fabricated using deuterated fluoromethacyrate, 5,6 UV curable fluorinated acrylate, 3 deuterated polysioxane, 7 and fluorinated polyimides. 9,10 Fluorinated poly(arylene ethers) developed for interlayer dielectric materials 11,12 are good candidate materials for the optical waveguide devices due to their excellent thermal stability, mechanical properties, low moisture absorption, and low inherent optical absorption at the near-infrared region. However, they did not show good chemical resistance for the multicoated thin-film process and sharp-cleaving property for optical fiber coupling at the end face of a device.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] The most widely studied PIs for optical applications are fluorinated ones, which exhibit the good processability, thermal stability, low dielectric constants and refractive indices, combined with good transparency in the visible region as well as at the near infrared wavelengths for telecommunication (1.3 mm and 1.55 mm). [7][8][9] Although a variety of PIs for optical applications have been reported, sulfur-containing polyimides have rarely been introduced. 10,11 In fact, sulfur-containing polymers, such as poly(methacrylates), [12][13][14] epoxy, 15 and polyurethane, 16,17 have been used for plastic lens, films and optical components.…”
mentioning
confidence: 99%
“…[1][2][3] One of the critical considerations for an optical polymer is low optical loss at the optical telecommunication wavelengths of 1.3 and 1.55 m. It is known that loss at near-infrared (IR) wavelengths is mainly attributed to absorption from vibrational overtones of the carbon-hydrogen (COH) bond, and this loss can be reduced appreciably by the substitution of hydrogen atoms to deuterium or fluoride. [4][5][6][7] Because the optical waveguides consist of a light carrying core and a cladding, another important requirement for the optical polymer is precise control of the refractive indices of polymers. It is reported that the copolymerization of fluorinated and nonfluorinated monomers provides good methodology to control the refractive indices of polymers.…”
Section: Introductionmentioning
confidence: 99%